New CCL|MPL Architecture Reducing Interfacial Gaps and Enhancing PEM Fuel Cell Performance. Issue 2 (26th February 2020) - Daniel, L.; Bonakdarpour, A.; Sharman, J.; Wilkinson, D. P.
Abstract: We demonstrate an enhanced new architecture for fuel cell membrane electrode assemblies (MEAs), by deposition of the microporous layer (MPL) directly on the catalyst coated membrane (CCM), in order to reduce any gaps at the cathode catalyst layer (CCL) surface. A low bonding temperature Teflon was used to allow low temperature sintering of the CCM with the MPL. This modified structure enhances PEMFC performance by improving the electronic contact and minimizing water pooling at the CCL|MPL interface. The improvement in water management at the CCL|MPL is beneficial especially for thinner CCLs to fulfill the performance demand with low cathode catalyst loading MEAs (≤0.125 mgPt cm −2 as targeted by the US Department of Energy).